Rancang Bangun Aplikasi Web Prakerin SMKN 2 Kabupaten Tangerang Menggunakan Framework Codeigniter - Sri Rahayu; Euis Nurninawati; Sigit Wahyudi (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2022)
Industrial Work Practice An activity carried out by Vocational High School students every second year of learning, the purpose of this Industrial Work Practice activity is to train students by studying and seeking by direct practice in the industrial world so that they can adapt to the industrial world after graduation. In the implementation of this Prakerin, there must be a system that processes all the data of students who take part in the implementation of Prakerin. The data management system that is currently running is still using Microsoft Excel, the use of the software is considered less than optimal and still has problems. Among other things, input data which takes a long time because all the data entered by the admin, besides that the internship activity journal still uses books, it has problems if the book is lost, or damaged, the school must replace the new book to the student concerned. Based on the problems found in the running system, the author designed a web-based student data management application system, using the PHP programming language with the Codeigniter framework, for database management using MySQL. After the new system, the data input process is expected to run more effectively because it is carried out by all prakerin students, then to fill in the internship activity journal it can be done directly on the prakerin web that has been designed. Keywords—Prakerin; Student; Industry; System; School Praktik Kerja Industri Merupakan kegiatan yang dilakukan oleh siswa Sekolah Menengah Kejuruan setiap tahun ke dua pembelajaran, tujuan dari kegiatan Praktik Kerja Industri ini yaitu melatih siswa dengan belajar dan mencari pengalaman dengan praktik langsung di dunia industri supaya dapat beradaptasi dengan dunia industri setelah siswa lulus nanti. Pada pelaksanaan Prakerin ini pastinya harus ada sistem yang mengolah seluruh data siswa yang mengikuti pelaksanaan Prakerin. Sistem pengelolaan data yang berjalan saat ini masih menggunakan Microsoft Excel, penggunaan software tersebut dirasa kurang optimal dan masih memiliki kendala. Diantaranya input data yang membutuhkan waktu yang lama karena seluruh data diinput oleh admin, selain itu jurnal kegiatan prakerin masih menggunakan buku hal tersebut memiliki kendala jika buku hilang, atau rusak maka pihak sekolah harus mengganti buku yang baru kepada siswa yang bersangkutan. Berdasarkan masalah yang terdapat pada sistem yang berjalan penulis merancang sistem aplikasi pengelolaan data siswa berbasis web, menggunakan bahasa pemrograman PHP dengan framework Codeigniter, untuk pengelolaan databasenya menggunakan MySQL. Setelah adanya sistem yang baru proses input data diharapkan dapat berjalan lebih efektif karena dilakukan oleh seluruh siswa prakerin, lalu untuk mengisi jurnal kegiatan prakerin dapat dilakukan langsung pada web prakerin yang telah dirancang. Kata Kunci—Prakerin; Siswa; Industri; Sistem; Sekolah